Alterations in NMDA receptor subunit densities and ligand binding to glycine recognition sites are associated with chronic anxiety in Alzheimer's disease - Tsang, Shirley WY (ELSEVIER SCIENCE INC, 2021)
10.1016/j.neurobiolaging.2007.03.014